The Blue Card impasse: Three options for EU policy on highly qualified immigrants - Steffen Angenendt; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2010)
In May 2009, after long and difficult negotiations, the EU Member States agreed on common rules to govern the immigration of highly qualified workers from outside the Union. Even before its entry into force, however, the Directive has become the target criticism. Many observers consider the program inadequate to meet the EU's large and growing need for high-skilled workers. Analysis of the failure of the Euro-pean Commission's more far-reaching proposals reveals three ways out of the current deadlock. The options include promoting forms of cooperation on immigration policy that preserve national sovereignty, better utilizing domestic labor potential, and creating an EU education market to induce high-potential foreign nationals to study and remain in the EU
Keywords: 320